(untitled) (Medico Legal Update, 2020)
Background: Avian influenza is very important contagious disease caused by Avian Influenza A viruses which continue to pose real threats for both human and animal. The virus subdivided into many HA and NA subtypes, some of them are highly pathogenic while others are low pathogenic for poultry. Method: Nasal swabs or fresh tracheal swabs in case of dead birds were taken from 417of chicken farms and flocks besides to 689 of local poultry that grew in the backyards all over Iraq to detect and identify viral subtypes. Results: Avian influenza viruses were observed in 7.04% of commercial chicken farms and in 4.93% of local poultry that growing in the backyards at Iraq; following subtypes were recorded: H9N2, H5N1, H7N9, H5N8 and H5N2. Subtype H9N2 is the prevalent type, all infections with H5N1, H5N8 and 28.57% of H7N9 subtypes were highly pathogenic; 100% of infections with H9N2, H5N2 and 71.42% of H7N9 appeared as low pathogenic. Conclusions: According to the author’s knowledge, the present study is first study recordedavian Influenza virus subtypes: H5N1, H7N9, H5N8 and H5N2 in domestic birds at Iraq.